Some Characterizations of k-Strictly Convex and k-Smooth Banach Spaces. (6th February 2019) - Wulede, Suyalatu
Abstract : In this paper, some characterizations ofk -strictly convex (k -smooth, respectively) spaces are given. As special cases fork = 1, some characterizations of strictly convex (smooth, respectively) spaces are given.